2012
DOI: 10.1007/s12610-012-0170-7
|View full text |Cite
|
Sign up to set email alerts
|

Dysfonction érectile et diabète : fréquence et profil clinique à partir de 200 observations

Abstract: Résumé Objectif la dysfonction érectile (DE) est une des complications les plus fréquentes du diabète mais également une des plus sous-diagnostiquées. Les auteurs rapportent la fréquence et le profil clinique de la DE dans une population de patients diabétiques. Patients et méthodes 200 patients diabétiques ont été évalués par l’Index international de la fonction érectile 5 (IIEF5) dans sa traduction française. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
0
2
Order By: Relevance
“…However, the influence of antihypertensive treatments on the occurrence of erectile dysfunction could not be demonstrated in the present study. We did not find a relationship between erectile dysfunction and obesity although it has been described by some authors [21] as risk factors for erectile dysfunction. Monabeka et al [20] had found a relationship between abdominal obesity and the occurrence of erectile dysfunction.…”
Section: Prevalence Of Erectile Dysfunctioncontrasting
confidence: 77%
See 1 more Smart Citation
“…However, the influence of antihypertensive treatments on the occurrence of erectile dysfunction could not be demonstrated in the present study. We did not find a relationship between erectile dysfunction and obesity although it has been described by some authors [21] as risk factors for erectile dysfunction. Monabeka et al [20] had found a relationship between abdominal obesity and the occurrence of erectile dysfunction.…”
Section: Prevalence Of Erectile Dysfunctioncontrasting
confidence: 77%
“…In addition, high blood pressure was strongly associated with the occurrence of erectile dysfunction. Zakhama W et al also found the association of high blood pressure with erectile dysfunction [21]. However, the influence of antihypertensive treatments on the occurrence of erectile dysfunction could not be demonstrated in the present study.…”
Section: Prevalence Of Erectile Dysfunctioncontrasting
confidence: 64%